Endoscopic features of esophageal adenocarcinoma derived from short‐segment versus long‐segment Barrett's esophagus. Issue 2 (1st September 2019) - Yamasaki, Akira; Shimizu, Tomoki; Kawachi, Hiroshi; Yamamoto, Noriko; Yoshimizu, Shoichi; Horiuchi, Yusuke; Ishiyama, Akiyoshi; Yoshio, Toshiyuki; Hirasawa, Toshiaki; Tsuchida, Tomohiro; Sasaki, Yutaka; Fujisaki, Junko
Abstract: Background and Aim: The study aims to clarify the endoscopic features and clinicopathological differences in superficial Barret's esophageal adenocarcinoma (s‐BEA) derived from short‐segment Barrett's esophagus (SSBE) and long‐segment Barrett's esophagus (LSBE). Methods: We reviewed data of 130 patients (141 lesions) with pathologically confirmed s‐BEA (SSBE: 95 patients and 95 lesions; LSBE: 35 patients and 46 lesions). We analyzed endoscopic and clinicopathological features of s‐BEA in patients with SSBE and LSBE. Results: The distribution of lesions according to macroscopic findings were as follows (s‐BEA in SSBE vs LSBE): flat type (0‐IIb), 3.2% (3/95) vs 32.6% (15/46) ( P < 0.001); accompanied type 0‐IIb, 2.1% (2/95) vs 21.7% (10/46) ( P < 0.001); and complex type (0‐I + IIb, 0‐IIa + IIc, etc.), 30.5% (29/95) vs 50.0% (23/46) ( P = 0.025). Complex‐type s‐BEAs had high incidences of T1b invasions and poorly differentiated components (simple type: 22.5% [20/89] and 18.0% [16/89]; complex type: 59.6% [31/52] and 44.2% [23/52], P < 0.001 and P = 0.002, respectively). In SSBE, 72.6% (69/95) of lesions were located at the right anterior wall ( P = 0.01). All flat‐type or depressed‐type lesions derived from SSBE were identified as reddish areas, whereas only 65.2% (15/23) from LSBE were identified as reddish areas ( P < 0.001). Conclusions: In LSBE, flat‐type, accompanied‐type 0‐IIb, and complex‐type lesions were significantly more prevalent. Furthermore, complex‐type s‐BEAs tended to have T1b invasions and poorly differentiated components. S‐BEAs in LSBE should be more carefully evaluated on endoscopic appearance including flat‐type and complex‐type lesions than in SSBE.